2019
DOI: 10.1007/s42010-019-00046-7
|View full text |Cite
|
Sign up to set email alerts
|

SRL in der Tasche? – Eine SRL-Interventionsstudie im App-Format

Abstract: Zusammenfassung Obwohl es bereits einige Studien gibt, die für die Effektivität von App-Interventionen im Bildungskontext sprechen, gibt es bisher keine systematisch evaluierte App zur Förderung von SRL. Im vorliegenden Beitrag wird eine Pilotstudie zu einer SRL-Intervention im App-Format zur Unterstützung von Studierenden beim Schreiben ihrer Bachelorarbeit vorgestellt. Interventionsziel war die Förderung von Wissen zu und Anwendung von metakognitiven SRL-Strategien sowie motivationalen Kompetenzen. In einem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
(47 reference statements)
0
1
0
1
Order By: Relevance
“…Given that smartphone, tablet, or computer apps are easily accessible and everyday tools, especially by students (Kortabitarte et al, 2018;Hartley et al, 2020), studies have identified that using smartphones in the service of learning generates positive academic outcomes (Anshari et al, 2017;Nguyen et al, 2018;Ariel and Elishar-Malka, 2019;Dalvi-Esfahani et al, 2020) and that using them for non-academic purposes (e.g., to check virtual social networks) burdens students' cognitive resource management by being a source of distraction when studying and when performing academic tasks outside of class (May and Elder, 2018;Aharony and Zion, 2019), which is associated with lower academic performance (Lepp et al, 2015;Chen and Yan, 2016). A small, recent body of research evaluates the impact of asking students to self-regulate their learning using apps (Xu et al, 2018;Foerst et al, 2019;Hendikawati et al, 2019;Kim et al, 2019;Loeffler et al, 2019;Broadbent et al, 2020;Hartley et al, 2020). Lobos et al (2021a) used the self-regulation of learning model proposed by Zimmerman (2002) to design the 4Planning app for smartphone, with the aim of evaluating its impact on the SRL of 473 1st-year engineering students in face-to-face mode, belonging to seven Chilean universities, during the first semester of 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Given that smartphone, tablet, or computer apps are easily accessible and everyday tools, especially by students (Kortabitarte et al, 2018;Hartley et al, 2020), studies have identified that using smartphones in the service of learning generates positive academic outcomes (Anshari et al, 2017;Nguyen et al, 2018;Ariel and Elishar-Malka, 2019;Dalvi-Esfahani et al, 2020) and that using them for non-academic purposes (e.g., to check virtual social networks) burdens students' cognitive resource management by being a source of distraction when studying and when performing academic tasks outside of class (May and Elder, 2018;Aharony and Zion, 2019), which is associated with lower academic performance (Lepp et al, 2015;Chen and Yan, 2016). A small, recent body of research evaluates the impact of asking students to self-regulate their learning using apps (Xu et al, 2018;Foerst et al, 2019;Hendikawati et al, 2019;Kim et al, 2019;Loeffler et al, 2019;Broadbent et al, 2020;Hartley et al, 2020). Lobos et al (2021a) used the self-regulation of learning model proposed by Zimmerman (2002) to design the 4Planning app for smartphone, with the aim of evaluating its impact on the SRL of 473 1st-year engineering students in face-to-face mode, belonging to seven Chilean universities, during the first semester of 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Des Weiteren können Smartphone-Apps vor allem die indirekte Förderung von Kompetenzen des selbstregulierten Lernens erweitern. Forschung zu einer derartigen Förderung ist bisher allerdings rar, und Smartphone-Apps scheinen vorrangig auf die Motivation von Schüler*innen zu wirken (Foerst, Pfaffel, Klug, Spiel & Schober, 2019;Loeffler, Bohner, Stumpp, Limberger & Gidion, 2019).…”
Section: Selbstreguliertes Lernen Im Präsenz-und Im "Fernunterricht"unclassified